MENGGUNAKAN KARTU KATA UNTUK MENINGKATKAN PENGUASAAN ATURAN PERUBAHAN NADA â€œYIâ€ DAN â€œBUâ€ DI SMA - Pasaribu, Susi Lestari; Ina, Ina; Kion, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractTone is very important in Mandarin, because the tone has the benefit of distinguishing meaning. Mandarin has four tones, and under certain conditions some characters will experience tone changes, for instance tone change of